1998
DOI: 10.1016/s0002-9440(10)65601-5
|View full text |Cite
|
Sign up to set email alerts
|

Production of Vascular Endothelial Growth Factor by Murine Macrophages

Abstract: Murine thioglycolate-induced peritoneal macrophages (MPMs) and the murine RAW264.7 macrophage-like cell line (RAW cells) constitutively produce vascular endothelial growth factor (VEGF). VEGF production is increased under hypoxic conditions or after cell activation with interferon-gamma (IFNgamma) and endotoxin (lipopolysaccharide, LPS). In contrast, tumor necrosis factor-alpha is produced only by IFNgamma/LPS-activated cells. Lactate (25 mmol/L) does not increase VEGF production by these cells. However, hypox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
75
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(87 citation statements)
references
References 43 publications
8
75
1
Order By: Relevance
“…Among the other fractions, fractions 9-11 also showed strong inhibitory activities but had no cytotoxic effects. The inhibitory effects of other fractions were much weaker, especially the last four fractions (12)(13)(14)(15), which contained high-polarity constituents.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Among the other fractions, fractions 9-11 also showed strong inhibitory activities but had no cytotoxic effects. The inhibitory effects of other fractions were much weaker, especially the last four fractions (12)(13)(14)(15), which contained high-polarity constituents.…”
Section: Resultsmentioning
confidence: 94%
“…10,11) It has been reported that NO is also involved in the production of vascular epidermal growth factor (VEGF), 12) the overexpression of which induces angiogenesis and vascular hyperpermeability, and accelerates tumor development.…”
mentioning
confidence: 99%
“…VEGF mRNA expression is up-regulated by LXR agonists both in the presence and absence of LPS. Although VEGF has been reported to be responsive to NFB activation (19,20), it is also regulated by many other pathways. Unlike iNOS, VEGF expression in murine macrophages is not highly dependent on NFB (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although resting monocytes and macrophages exhibit a nonangiogenic phenotype under normoxic conditions, hypoxia, elevated lactate levels, and inflammation strongly stimulate VEGF production (18). Treatment with bacterial lipopolysaccharide (LPS) or with CD40L stimulates VEGF production in human primary macrophages (19). This effect has been reported to be NFBdependent, because it is sensitive to the overexpression of the inhibitory protein, IB␣ (20).…”
mentioning
confidence: 99%
“…VEGF is produced by a broad range of cell types, including macrophages, platelets, and neutrophils (4). The expression of VEGF is regulated by various stimuli, such as inflammatory cytokines (interleukin-1, tumor necrosis factor alpha, gamma interferon), hypoxia, and lipopolysaccharide (11,18). The first line of defense against pneumococci consists predominantly of neutrophils.…”
mentioning
confidence: 99%